Spatio-temporal changes of Munida Rutllanti Zariquiey-Alvarez, 1952 (Decapoda: Galatheidae) in the North-Western Ionian Sea (Central Mediterranean) - MAIORANO, P.; CAPEZZUTO, F.; D’ONGHIA, G.; TURSI, A. (Mediterranean Marine Science, 2013)
The spatio-temporal pattern of Munida rutllanti distribution in the north-western Ionian Sea has been studied. Data were collected during 14 experimental trawl surveys conducted from 1997 to 2010 as part of the international MEDITS project. The hauls were carried out during day-light hours between depths of 10 and 800 m in the spring season. A progressive increase in the abundance index (N/km2) of M. rutllanti was observed from 2000 to 2008, then a sharp decrease was shown in the last two years. The greatest and lowest abundance indices were observed in the Apulian and central Calabrian sub-areas, respectively. The species was collected between 107 and 795 m in depth, with a significant increase and decrease over time in the maximum and minimum depth of finding, respectively. A highly significant increase over time in the mean carapace length was also observed in the whole study area. The widespread occurrence and increasing abundance of this species in the Ionian Sea could be related to the increase in temperature and the variation in hydrographic conditions which occurred in the Ionian basin during the EMT-BiOS phenomenon.